Modeling nonlinear viscoelastic nanoindentation of PVAc at different unloading rates - Kucuk, Yilmaz (Strojniški vestnik, 2013)
In this study, nanoindentation technique was used to determine the nonlinear viscoelastic behavior of polyvinyl acetate (PVAc) with a glass transition temperature of 29 °C. Nanoindentation was conducted with a Berkovich nanoindenter tip under the same constant loading rate but different unloading rates. The Burgers nonlinear viscoelastic model was implemented in ABAQUS/Standard finite element code by means of a user-defined subroutine. After fitting the complete load-displacement curves, parameters in the nonlinear Maxwell and Voigt elements were obtained to describe the nonlinear viscoelastic behavior of PVAc. The results show that PVAc exhibits negative unloading stiffness under low unloading rates. However, if the unloading rate is higher than 0.1 mN/s, PVAc appears more elastic behavior. The nonlinear Burgers model used can successfully model the nonlinear viscoelastic behavior of PVAc at different unloading rates, including the unloading nose associated with negative unloading slope at slow unloading rate for a highly viscoelastic material.
Keywords: FEM; finite element method; finite element simulation; metoda končnih elementov; nanoindentacija; nanolinear viscoelastic nanoindentation; nelinearni Burgesov model; nonlinear Burgers model; PVAc; viscoelasticity; viskoelastičnost